Kebijakan Lima Hari Sekolah dan Implikasinya pada Guru Pendidikan Agama Kristen - Riwu Wulan (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2023)
The five-day school policy caused controversy from various parties which the government then addressed by issuing a Character Strengthening Program policy as an affirmation of the goals of the five-day school policy. Christian Religion teachers have a major role in strengthening students’ character so that the five-day school policy has serious implications for Christian Religion teachers. Using the Systematic Literature Review method, this study aims to explore the link between the five-day school policy and the role of Christian Religion teachers in strengthening students’ character. Based on the results of the analysis it was found that Christian Religion teachers have important roles to play in the success of the five-day school policy and must carry out their roles properly as guides, motivators, parents, and role models for students. Christian Religion teachers must also be able to become interpreters of the Christian faith, shepherds and evangelists for their students. If Christian Religion teachers carry out their roles well, the process of strengthening students’ character in the implementation of the five-day school policy will also run well. Christian Religion teachers can actualized the strengthening of students’ character in three ways, namely intra-curricular, co-curricular and extra-curricular activities so that students’ character can be built optimally at school. Kebijakan lima hari sekolah menimbulkan kontroversi dari berbagai pihak yang kemudian disikapi oleh pemerintah dengan mengeluarkan kebijakan Program Penguatan Karakter sebagai penegasan tujuan dari kebijakan lima hari sekolah tersebut. Guru Pendidikan Agama Kristen memiliki peran yang besar dalam penguatan karakter siswa sehingga kebijakan lima hari sekolah memiliki implikasi yang serius bagi guru PAK. Dengan menggunakan metode Systematic Literature Review, penelitian ini bertujuan untuk mengupas kaitan kebijakan lima hari sekolah dengan peran guru Pendidikan Agama Kristen dalam penguatan karakter siswa. Berdasarkan hasil analisis didapati bahwa Guru PAK memiliki peran penting untuk menyukseskan kebijakan lima hari sekolah dan harus menjalankan perannya dengan baik sebagai pembimbing, motivator, orangtua,serta teladan bagi siswa. Guru PAK juga harus mampu menjadi penafsir iman Kristen, gembala dan penginjil bagi siswanya. Apabila peran guru PAK ini dilaksanakan dengan baik maka proses penguatan karakter siswa dalam implementasi kebijakan lima hari sekolah juga akan berjalan dengan baik. Guru PAK dapat mewujudkan penguatan karakter siswa dalam tiga hal yaitu kegiatan intrakurikuler, kokurikuler dan ekstrakurikuler agar karakter siswa dapat dibentuk secara optimal di sekolah.